Convention on the Rights of Persons with Disabilities - United Nations (OHCHR, 2006)
Entry into force: 3 May 2008, in accordance with article 45(1). Preamble (a) Recalling the principles proclaimed in the Charter of the United Nations which recognize the inherent dignity and worth and the equal and inalienable rights of all members of the human family as the foundation of freedom, justice and peace in the world,
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Freedom of Information Around the World 2006: A Global Survey of Access to Government Information Laws - Banisar, David (Privacy International, 2006)
Keywords: References - Boel et al. (2021), Archives and Human Rights; References - Comma (2020 1-2), Archives and Human Rights